The effect of sodium metabisulfite concentration on the physicochemical stability of an L-Ascorbic Acid face mist formulation - Siska Anastasia, Desy; Desnita, Rise; Yuswar, Muhammad Akib; Halim, Clara Maretta (Universitas Mataram, 2025)
Face mist is a cosmetic that is included in skin fresheners, is more practical to use, and has the potential to add antioxidants. Vitamin C is one source of antioxidants. Although water-soluble, vitamin C is an antioxidant that oxidizes readily. Sodium metabisulfite must be added to prevent oxidized vitamin C from becoming unstable. Topical treatments containing 0.01–1.0% sodium metabisulfite act as antioxidants. Therefore, a face mist preparation was made with variations in the concentration of sodium metabisulfite, namely 0.25%, 0.5%, and 1%. This study aims to see an increase in the stability of vitamin C face mist preparations with an increase in the concentration of sodium metabisulfite through physicochemical stability testing under real-time storage conditions for 28 days. The parameters to be observed in the stability test include organoleptic test, pH, specific weight, viscosity, and vitamin C levels. The F1 formula with the smallest concentration of sodium metabisulfite (0.25%) has been able to maintain the stability of vitamin C face mist preparations for 28 days of storage